Performance of MSMEs with Disabilities: Digital Financial Inclusion as an Intermediary for Digital Transformation and Financial Literacy - Nugroho, Dwiyanjana Santyo; Alamin, Ahmad Fikri; Anita, Anita; Krisnandika, Verina Ruth (STIE Tri Bhakti, 2025)
This study aims to analyze the influence of digital transformation and financial literacy on the performance of Micro, Small, and Medium Enterprises (MSMEs) with disabilities in DKI Jakarta, with digital financial inclusion as a mediating variable. Primary data were collected from 30 respondents who are MSME actors with disabilities using questionnaires and analyzed with Structural Equation Modeling – Partial Least Squares (SEM-PLS). The outer model test results confirmed the validity and reliability of the instruments. However, key findings from the inner model test indicate that digital transformation significantly and negatively affects both digital financial inclusion and the performance of MSMEs with disabilities. Meanwhile, financial literacy does not significantly influence either digital financial inclusion or the performance of MSMEs with disabilities. Digital financial inclusion was not proven to mediate the relationship between digital transformation and financial literacy on the performance of MSMEs with disabilities. The implications of this study indicate that the current digitalization efforts and financial literacy levels among MSMEs with disabilities in DKI Jakarta are not yet optimal or even pose challenges, thus failing to effectively enhance performance. This study emphasizes the urgency of more inclusive and adaptive assistance programs to ensure positive digital transformation implementation and optimized utilization of digital financial services for MSMEs with disabilities.